Rancang Bangun Aplikasi untuk Menentukan Jalur Terpendek Rumah Sakit di Purbalingga dengan Metode Algoritma Dijkstra - Abdul Ghofur Wibowo; Agung Purwo Wicaksono (JUITA : Jurnal Informatika, 2012)
Application of  Dijkstra's algorithm  is an  application made  to  determine the shortest path of hospital in  Purbalingga where the starting point comes from  a single point, namely  the town square of Purbalingga. The system is made with Microsoft Visual Studio 2005 and Microsoft SQL Server 2005.There are two types of hospitals in Purbalingga, such us public hospital and maternal hospital. On the main page, user can specify the type of hospital first before determining the choice of destination hospital. After that, user can know the shortest way to go. There is also a digital map in order to facilitate user into the hospital and information obtained is more informative. On the admin page is used to add data path information, hospital data and map data. Besides, the data path and hospital data can be changed if an error occurs. To determine the shortest path from each hospital, administrator must enter data into  the  system calculated  to form and then saved to the database, which will be used as a user's  information  can be obtained after choosing the destinationhospital